Analisis Kelayakan Usaha dengan Metode Diskonto dan Tanpa Diskonto: Studi Kasus UMKM Kedai Sera - Prabumulya, Rizkillah Aji; Nitisara, Naurah Wafa; Clara, Dinda; Aurelia, Sabila; Liliany, Azzahra Wani; Dian Fajarini (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This study aims to analyze the business feasibility of the Kedai Sera MSME located in Bandar Lampung City using both discounted and non-discounted methods. A descriptive quantitative approach was applied, utilizing primary data in the form of Kedai Sera’s annual financial statements for the period 2018–2024. The non-discounted method includes analysis using Payback Period, Break-Even Point (BEP), and Revenue-Cost (R/C) Ratio. Meanwhile, the discounted method employs Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (B/C) as indicators. The analysis results show that based on the non-discounted method, the business has a Payback Period of 2 years, a BEP of 1,530 units, and an R/C Ratio of 3.27, indicating that the business is feasible and efficient to operate. Furthermore, using the discounted method, the NPV is IDR 211,434,376 and the IRR is 31.9824%, which exceeds the discount rate of 11.25%, indicating financial feasibility. The Net B/C Ratio is < 1, suggesting that Kedai Sera’s business is feasible for development.